Emerging Evasion Mechanisms of Macrophage Defenses by Pathogenic Bacteria - Leseigneur, Clarisse; Lê-Bury, Pierre; Pizarro-Cerdá, Javier; Dussurget, Olivier (Frontiers in Cellular and Infection Microbiology, 2020)
Macrophages participate to the first line of defense against infectious agents. Microbial pathogens have evolved sophisticated mechanisms to escape macrophage killing. Here, we review recent discoveries on bacterial molecular strategies to subvert macrophagic immune reponses. We focus on Listeria monocytogenes, Staphylococcus aureus and Yersinia pestis to illustrate the diversity of mechanisms used by microorganisms with different pathogenic lifestyles.